STRATEGI PROMOSI ONLINE INSTAGRAM DAN STRATEGI HARGA UNTUK MENINGKATKAN MINAT BELI JASA PENERBANGAN AIR ASIA RUTE JAKARTA - SINGAPURA - Marsadi Aras; Ahmad Nurdin Hasibuan; Suci Fatihah; Delila Rambe (Mediastima, 2021)
This study aims to analyze the effect of promotional strategies using social media and price strategies with the interest in buying airline services on the Jakarta-Singapore route of AirAsia. This study applies a survey by taking samples directly to the population. This research uses a causality design, to analyze the influence of the Instagram online promotion variable and the price strategy to increase buying interest, through hypothesis testing. Respondents were determined by non-probability technique with purposive judgment sampling method. The results showed that the promotion strategy through Instagram social media had a positive and significant effect on purchasing decisions. A positive t value indicates that the promotion variable through Instagram social media has an effect that is directly proportional to purchase intention. pricing strategy has a positive and significant effect on purchasing decisions. A positive t value indicates that the price variable has an effect that is directly proportional to purchase intention. Promotion through Instagram social media and price strategy simultaneously have a positive and significant effect on purchase intention. Instagram Online Promotion Strategy, Price Strategy, Purchase Intention